2006
DOI: 10.1074/jbc.m606693200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Atypical MAPK ERK4 and Its Activation of the MAPK-activated Protein Kinase MK5

Abstract: The extracellular-regulated kinase (ERK) 4 (MAPK4) and ERK3 (MAPK6) are structurally related atypical MAPKs displaying major differences only in the C-terminal extension. ERK3 is known as an unstable mostly cytoplasmic protein that binds, translocates, and activates the MAPK-activated protein kinase (MK) 5. Here we have investigated the stability and expression of ERK4 and have analyzed its ability to bind, translocate, and activate MK5. We show that, in contrast to ERK3, ERK4 is a stable protein that binds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(133 citation statements)
references
References 20 publications
5
115
0
2
Order By: Relevance
“…Wild-type GFP was found to be stable in mammalian cells with a half-life of 26 h but can be destabilized by the fusion with proteins with shorter half-lives (Corish and Tyler-Smith 1999;Kant et al 2006). Furthermore, it has been shown that, in HEK293 cells, the stability of ERK3 protein that is degraded by the proteasome was independent of the presence of the Nterminal GFP tag (Kant et al 2006). Thus, the half-lives calculated for GFP-3a and GFP-3a-FRAA are probably closely related to the half-lives of wild-type eRF3a and eRF3a-FRAA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type GFP was found to be stable in mammalian cells with a half-life of 26 h but can be destabilized by the fusion with proteins with shorter half-lives (Corish and Tyler-Smith 1999;Kant et al 2006). Furthermore, it has been shown that, in HEK293 cells, the stability of ERK3 protein that is degraded by the proteasome was independent of the presence of the Nterminal GFP tag (Kant et al 2006). Thus, the half-lives calculated for GFP-3a and GFP-3a-FRAA are probably closely related to the half-lives of wild-type eRF3a and eRF3a-FRAA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…MAPK4 and its homolog, ERK3, are classified as atypical MAPKs, both of which activate MK5 (Seternes et al 2004;Aberg et al 2006Aberg et al , 2009Gaestel 2006;Kant et al 2006;Deleris et al 2008;Perander et al 2008). Notably, ERK3 protein is rapidly turned over, whereas MAPK4 is not (Aberg et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK4 activates MK5 by phosphorylating the latter at T182, resulting in cytoplasmic accumulation of MK5 (Kant et al 2006;Coulombe and Meloche 2007;Deleris et al 2008;Perander et al 2008;Aberg et al 2009). MK5, in turn, phosphorylates HSP27 (HSPB1) and was suggested to thereby induce altered microfilament organization Doshi et al 2010).…”
Section: Igf2bp1 Antagonizes the Phosphorylation Of Hsp27 By Interfermentioning
confidence: 99%
“…No phosphorylation at Ser-15 was detected. Atypical MAP kinases ERK3 and ERK4 bind to and activate MK5 [67][68][69][70] and MK5 coimmunoprecipitates from murine heart lysates with ERK3, but not ERK4 or p38α [36]. Furthermore, MK5 may also be activated by PKA.…”
Section: Discussionmentioning
confidence: 99%